Behavioral Differences among Eastern Bluebird Populations Could Be a Consequence of Tree Swallow Presence: A Pilot Study - Albers, Alexandria N.; Jones, John Anthony; Siefferman, Lynn (Frontiers in Ecology and Evolution, 2017)
Aggressive interference competition for limited resources is frequently observed among animals. However, these behavioral interactions within (intraspecific) and between (interspecific) species are costly as they can be energetically expensive and cause injury or death. To avoid these agonistic interactions, numerous species alter their behaviors and resource requirements. Spatial variation in nest site competition allows for investigation of concurrent variation in territorial defense behavior. Further, among species with bi-parental nest defense, behavioral similarity in territorial defense may benefit pairs. Here, we studied territorial aggression between two eastern bluebird (Sialia sialis) populations (North Carolina and Alabama, USA) that differ in avian community structure; those in North Carolina have recently begun to experience strong interspecific competition for nesting cavities by tree swallows (Tachycineta bicolor), a competitive pressure that is relatively new for North Carolina bluebirds ( 35-40 years) and is absent in Alabama populations. We found that bluebirds in North Carolina are more aggressive to simulated territorial intrusions compared to their Alabama counterparts. Behavioral similarity (here, in aggression) between partners is strong and similar in both populations. These results suggest that bluebirds in North Carolina may have to maintain higher baseline aggression during territory establishment and nest construction to co-occur with highly aggressive tree swallows, but that, in both populations, behavioral similarity between partners may be adaptive. Finally, we acknowledge the preliminary nature of this study and the need for expanding the behavioral studies to other sites in the southeastern United States. Greater regional coverage would exclude the possibility of alternative drivers of the observed behavioral differences between the North Carolina and Alabama populations.